SIXTEEN PROPERTIES OF Eucalyptus tereticornis WOOD FOR STRUCTURAL USES - Jesus Albuquerque Nogueira, Marta Cristina de; Araujo, Victor Almeida de; Vasconcelos, Juliano Souza [UNESP]; Christoforo, Andre Luis; Rocco Lahr, Francisco Antonio (Univ Federal Uberlandia, 2020)
Forest Red Gum eucalypt provides a versatile wood and is converted into different purposes. However, such wood is somewhat limited in structural ends, which highlights the need to exploit this gap through diffusion of mechanical properties of such timber. This study aimed to evaluate the effect of moisture content reduction, from 30 to 12%, in physical and mechanical properties of Eucalyptus tereticornis, using Brazilian and American documents, to reinforce the structural potential wood and assisting engineers and architects in decision-making for its best building application. We evaluated two physical and fourteen mechanical properties of Eucalyptus tereticornis at two different moisture contents, following the prescriptions of Brazilian (ABNT NBR 7190: 1997) and North American (ASTM D-143-14: 2014) standards. Thus, 1091 repeats were carried out for all properties. By a moisture reduction, the bulk density and eleven strength properties statistically showed changes such as modulus of rupture (static bending, parallel and perpendicular compressions), modulus of elasticity (perpendicular compression and static bending), shear stress, tangential cleavage, and parallel and perpendicular hardnesses. Then, the Eucalyptus tereticornis timber could be better usable if is further applied for structural construction uses.
Keywords: Eucalypt; Timber; Moisture content; Density; Strength